USM STRENGTHENS RELATIONS WITH HIROSHIMA UNIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 5 December 2016 – Universiti Sains Malaysia (USM) continues to strengthen relations with Hiroshima University (HU) with the visit of a 16member delegation from HU to the USM School of Educational Studies (PPIP) to participate in the International Students Colloquium 2016 here recently.